Cultural Integration on Students' Productivity During Distance Learning - Parmin, Parmin; Syafi, Mohammad Qois; Junaedi, Iwan; Yulianto, Agus; Purwantoyo, Eling; Mubarok, Ibnul (Jurnal Pendidikan dan Pengajaran, 2021)
This study aims to measure the effectiveness of cultural integration on the productivity of Mathematics and Natural Sciences students during the implementation of distance learning. The culture integrated into this research is a habit that becomes a society's tradition in behaving. The research problem is about the integration of culture on character formation, which impacts student productivity. The study used mixed methods with quantitative data from questionnaires and qualitative data from interviews and document analysis. The research targets are 344 students filled out the questionnaire. After the questionnaire data was analyzed, it was deepened through interviews. The relationship test between character strengthening and students' productivity obtained a correlation coefficient value of 0.59, indicating that the correlation between variables is quite strong. Internalization of cultural values into forming students' characters in distance lectures and activities is carried out through habituation. The selection of online application media refers to the ease of access, students' common use, and ease of operation. The research concludes that students' characters contribute to building students' self-awareness to be productive.